Acupuncture of different treatment frequencies in knee osteoarthritis: a pilot randomised controlled trial. Issue 11 (November 2020) - Lin, Lu-Lu; Tu, Jian-Feng; Wang, Li-Qiong; Yang, Jing-Wen; Shi, Guang-Xia; Li, Jin-Ling; Zhang, Na; Shao, Jia-Kai; Zou, Xuan; Liu, Cun-Zhi
Abstract : Abstract: This 16-week randomised controlled trial (8-week treatment followed by 8-week follow-up) evaluated the symptomatic improvement in patients with knee osteoarthritis on 3 sessions per week of acupuncture (TSWA) compared to 1 session per week of acupuncture (OSWA). Sixty participants were randomised to either the TSWA or the OSWA group in a 1:1 ratio. The primary outcome was response rate, defined as the percentage of participants achieving ≥2 points decrease on the numerical rating scale (NRS) and ≥6 points decrease in Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) function score at week 8 compared with baseline. Additional outcomes included response rates at weeks 4 and 16, NRS, WOMAC, Patient Global Assessment, 12-item Short Form Health Survey (SF-12), and treatment credibility and expectancy. No significant difference was seen in response rate between TSWA and OSWA groups at week 8 (64.7% vs 50.0%; difference, 14.7 percentage points [95% CI, −10.1 to 39.4 percentage points], P = 0.435). At weeks 4 and 16, the TSWA group had higher response rates than the OSWA group (week-4: difference, 44.7 percentage points [95% CI, 23.2-66.1 percentage points], P = 0.001; week-16: difference, 46.0 percentage points [95% CI, 24.4-67.6 percentage points], P < 0.001). Participants in the TSWA group experienced significantly greater improvements in NRS, WOMAC function, and Patient Global Assessment than those in the OSWA group. There were no significant between-group differences in WOMAC stiffness and SF-12. In summary, TSWA immediately improved knee pain and dysfunction compared with OSWA. In addition, the benefit of TSWA persists throughout follow-up. Abstract : Supplemental Digital Content is Available in the Text.In knee osteoarthritis, 3 sessions per week of acupuncture treatment offers benefit in improving knee pain and function compared with 1 session per week.